Calcium pretreatment enhances fluoride reactivity with enamel and dentine - Spinola, Manuela Da Silva; Tenuta, Livia Maria Andalo (Elsevier B.V., 2022)
Objective: High fluoride concentration treatments are known to react with enamel and dentine forming calcium fluoride (CaF2)-like deposits, but strategies to improve this reactivity beyond increasing fluoride concentration/ reducing pH in fluoride treatments have not been explored. Here we investigated the ability of a calcium pretreatment to improve fluoride reactivity.& nbsp;Design: In a blind and randomized in vitro study, sound and carious enamel and dentine slabs (n = 11/group) were randomly allocated into one of the following treatments: Deionized water (negative control); 0.05% sodium fluoride (F, positive control); 150 mM calcium lactate solution followed by 0.05% sodium fluoride solution (Ca-*F); 150 mM calcium lactate solution premixed with 0.05% sodium fluoride solution (CaF2, active control). Alkali-soluble fluoride (representing CaF2-like deposits formed on the substrates) was extracted from the slabs using 1 M KOH for 24 h and measured by an ion-specific electrode. Carious slabs were further observed under scanning electron microscopy (SEM). Data were analyzed by two-way ANOVA followed by Tukey test.& nbsp;Results: The Ca-*F treatment enhanced fluoride reactivity with all tested substrates when compared with F alone. Carious substrates had a greater reactivity with F and Ca-*F than their respective sound substrates, confirming that increased porosity enhances the reactivity with fluoride. Alkali-soluble fluoride concentration after the CaF(2 & nbsp;)treatment did not differ among the different substrates, suggesting this treatment causes only contamination with preformed CaF2, which was noted under SEM.& nbsp;Conclusion: A calcium pretreatment enhances the reactivity of fluoride with enamel and dentine.
Keywords: Fluoride; Calcium fluoride; Dental caries; Root; Prevention